Subtyping Recursive Types - Amadio, Roberto M.; Cardelli, Luca (ACM Transactions on Programming Languages and Systems, Proc. ACM Symp. Principles of Programming Languages, 1990)
We investigate the interactions of subtyping and recursive types in a simply typed łambda-calculus. The two fundamental questions here are whether two (recursive) types are in the subtype relation and whether a term has a type. To address the first question, we relate various definitions of type equivalence and subtyping that are induced by a model, an ordering on infinite trees, an algorithm, and a set of type rules. We show soundness and completeness between the rules, the algorithm, and the tree semantics. We also prove soundness and a restricted form of completeness for the model. To address the second question, we show that to every pair of types in the subtype relation we can associate a term whose denotation is the uniquely determined coercion map between the two types. Moreover, we derive an algorithm that, given a term with implicit coercions, can infer its least type whenever possible.